2005
DOI: 10.1186/1471-2296-6-52
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone use during intimate examinations in primary care: postal survey of family physicians

Abstract: Background: Physicians have long been advised to have a third party present during certain parts of a physical examination; however, little is known about the frequency of chaperone use for those specific intimate examinations regularly performed in primary care. We aimed to determine the frequency of chaperone use among family physicians across a variety of intimate physical examinations for both male and female patients, and also to identify the factors associated with chaperone use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 15 publications
10
39
0
Order By: Relevance
“…According to our findings, the use of chaperones varies greatly by type of examination with the whole body as well as pelvic and breast examinations the most likely to be observed by a chaperone. This was corroborated by previous published studies [6,15]. Using a chaperone has been shown to add both a layer of protection and acknowledgement of a patient's vulnerability [9,15].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…According to our findings, the use of chaperones varies greatly by type of examination with the whole body as well as pelvic and breast examinations the most likely to be observed by a chaperone. This was corroborated by previous published studies [6,15]. Using a chaperone has been shown to add both a layer of protection and acknowledgement of a patient's vulnerability [9,15].…”
Section: Discussionsupporting
confidence: 81%
“…However, our study captured only specialist doctors within 5 years of clinical practice and it is not impossible that the association may differ if our data included older practitioners. However, other previous studies did not report any age-related differences [6,13,15,17].…”
Section: Discussionmentioning
confidence: 58%
“…Several reasons have been suggested for the inadequate use of chaperones including, inter alia, the shortage of nursing staff to act as chaperones, 15 and a general lack of awareness. 16 This is certainly an area for improvement in our health care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries have shown that women are generally less interested in visiting service providers of the opposite sex for issues related to sexual and reproductive health (13). In addition, male personnel and physicians do not feel comfortable when doing examinations or taking women's history, and they use a chaperone, a person who accompanies them during physical examinations, much more than women physicians (26,27).…”
Section: Discussionmentioning
confidence: 99%